Teaching the social skills of academic interaction, grades 4-12 : - Daniels, Harvey (Corwin, 2014)
Teaching the Social Skills of Academic Interaction taps the instructional power of slides, full-color illustrations, and super succinct directions to teach both the language and the behaviors of working effectively with others. These 35 lessons take your kids on a carefully paced upward spiral of collaboration, with explicit coaching on how to speak, listen, argue, persuade—and get along. Here’s the best part: You model and your students practice these social skills with the content of your curriculum, not in disconnected add-on exercises.